(untitled) (Biological Sciences - PJSIR, 2002)
Different sweat orange products like juice, peel, coarse peel , fines of peel , lime treated peel, molasses extracted peel, juice sacs, molasses and skin (peel without juice sacs) etc. were developed at laboratory scale and dried in an electric oven. Maximum crude protein (7.5%), crude fat (5.27%) and ash (5.53%) contents were recorded in dried juice sacs. Moisture content of different dried products ranged between 7.44-13 .36%. Untreated peel contained highest amount of ascorbic acid (408.75 mglOOg ·1 and beta-carotene (25.98 mg g·1). All the products contained more than 1% pectin and its fractions showed some variation